THE URGENCY OF CHARACTER EDUCATION IN EDUCATIONAL UNITS IN INDONESIA IN FACING GLOBAL CHALLENGES AND 21ST CENTURY COMPETENCIES - Thomy Sastra Atmaja (Jurnal Scientia, 2023)
This study examines the urgency of character education in education units in Indonesia, especially in facing global challenges and meeting 21st century competencies. The method used is literature study, involving steps to determine the research topic, literature search, literature analysis, and conclusions. In the multicultural context of Indonesia, character education is very important to form mutual respect, tolerance, and mutual assistance in a diverse society. The focus on the role of character education as a shaper of national values and understanding of cultural diversity in Indonesia is explained in depth. Global challenges, such as the quality of education, teacher professionalism, cultural acculturation, and technological advancement, become important backgrounds for the urgency of character education. Character education is identified as a key instrument to equip individuals with the skills and values needed in the face of rapid change in the information age and globalization. Character education plays a key role in shaping leadership, creativity, and emotional toughness. Character values, such as tolerance, integrity, and openness, are integrated in learning to form individuals who can compete globally. The pillars of 21st century education affirm the importance of character values as the main foundation, and optimal implementation in schools is the key to overcoming the moral crisis and producing a generation of academically intelligent and integrity. Involving schools, families, and communities, character education is a shared responsibility in shaping Indonesia's golden generation.